Analisis Finansial Usahatani Kangkung Darat (Ipomoea Reptans Poir) Di Desa Karangmekar Kecamatan Kedungwaringin Kabupaten Bekasi - Rachma Merisya Purwatiningsih; Yusuf Muhyiddin; I Putu Eka Wijaya (Jurnal Ilmiah Wahana Pendidikan, 2022)
Kale production in Karangmekar Village is relatively high. The income of kale farmers should also be quite high, but in practice farmers experience many obstacles. These constraints resulted in kale farmers often experience losses. Therefore, it is necessary to conduct a financial feasibility study to find out whether kale farming provides a decent profit or not. The sampling technique was carried out using the census method, through calculations using financial analysis, Break Even Point (BEP), and R/C Ratio. The results of this study indicate: 1) The income of kale farming in 2 planting periods is equally profitable with the average income of each farmer of Rp. 1,124,366. 2) kale farming has reached the Break Even Point (BEP) with an average production BEP of 41.2 kg and a BEP price of Rp. 61,771. 3) The feasibility level (R/C Ratio) of kale farming in 2 planting periods is financially equally feasible to cultivate, with an average R/C Ratio of 1.33.